Pengaruh Kualitas Layanan terhadap Kepuasan dan Loyalitas Pengguna Brimo Menggunakan Model E-Service Quality - Adut, Fransiska Armelia; Ramadhan, Viry Puspaning (LPPM STIKI MALANG, 2024)
The purpose of this study is to evaluate the quality of service offered by Bank Rakyat Indonesia's (BRI) BRIMO application, and how this impacts user satisfaction and loyalty. The Servqual method was used to survey 100 students of Universitas Merdeka Malang (UNMER). The results showed that five dimensions of service quality-tangibles, responsiveness, reliability, empathy, and assurance significantly impacted user satisfaction and loyalty. The physical elements of the BRIMO application, specifically internet availability and system responsiveness, have a significant influence on user satisfaction and user loyalty. Users are more satisfied because of the BRIMO staff responsiveness to their feedback, while users feel more comfortable and satisfied that the privacy and security of their data is guaranteed. The ability of BRIMO employees to communicate well and provide full attention increases user satisfaction and user loyalty. This research shows that improving the service quality of digital banking apps is critical to maintaining user satisfaction and their loyalty.